Prevalence and knowledge, attitude and practices related to schistosomiasis among primary school children in Chaani village, North “A” District, Zanzibar - Haji, Kassim H.; Guddeti, Prashath K. (International Journal of Research in Medical Sciences, 2021)
Background: Schistosomiasis is a chronic, parasitic disease caused by blood flukes (Schistosoma species). It has been for along time a neglected tropical disease in most of the sub-Saharan countries. Methods: A cross sectional descriptive study was conducted between June 2015 to July 2015 at Chaani village in North “A” District. The school children were interviewed to identify activities which expose them frequently to water contact. Study subjects were selected by using stratified random sampling technique. The selected school children were asked to collect urine sample in well-labeled container. The samples were processed in the laboratory by using standard microbiological techniques (syringe filtration then examined by microscopy) and results were recorded, the data was analyzed. Results: Out of 170 School children 62 were infected with Schistosoma haematobium which is the predominant Schistosoma species found in that area. Among the 62, 45 (57.6%) were male and 17 (42.4%) were female. The level of knowledge of respondents on Schistosomiasis transmission is that 70% of school children have high knowledge, 18% have moderate knowledge and 12% have low knowledge. Other parameters were also assessed like bathing habits and knowledge and functions of Schistosomiasis control drug. Conclusions: Males were significantly more affected by the disease than females. Provision of safe water coupled with education of the communities regarding the modes of transmission of the disease and the way to prevent oneself, as well as provision of sanitary facilities, such as latrines may decrease the disease burden.